Anemia, leukocytosis and thrombocytosis as prognostic factors in patients with cervical cancer treated with radical chemoradiotherapy: A retrospective cohort study. (June 2017) - Koulis, Theodora A.; Kornaga, Elizabeth N.; Banerjee, Robyn; Phan, Tien; Ghatage, Prafull; Magliocco, Anthony M.; Lees-Miller, Susan P.; Doll, Corinne M.
Abstract: Introduction: Anemia has long been associated with poor prognosis in patients with cervical cancer. Recently, additional hematologic parameters have emerged as potential indicators of worse outcome in this patient group. In a cohort of cervical cancer patients treated with chemoradiotherapy (CRT) and brachytherapy, we report on the prognostic significance of hematologic parameters including anemia, leukocytosis, neutrophil to lymphocyte ratio (NLR), and thrombocytosis, the effect of combining anemia with other hematologic parameters, and the effect of changes in hemoglobin levels during treatment. Materials and methods: Two-hundred fifty-seven cervical cancer patients were retrospectively identified from a single cancer institution's database. Hematologic parameters were categorized as: anemia (hemoglobin ≤115 g/L), leukocytosis (white blood cell count >10 × 10 9 /L), thrombocytosis (platelets >400 × 10 9 /L), and NLR (ratio >5). The association between clinical factors and hematologic parameters on progression-free survival (PFS) and overall survival (OS) were assessed at 5 years. Results: At 5 years, both pre-treatment anemia (PFS: 60% vs 34%, p < 0.0001; OS: 68% vs 41%, p < 0.0001) and on-treatment anemia (PFS: 62% vs 40%, p < 0.0001; OS: 70% vs 48%, p < 0.0001) were significantly associated with worse survival. This adverse effect on 5-year PFS and OS was increased in patients with both pre-treatment anemia and leukocytosis (PFS: 72% vs 42%, p < 0.0001; OS: 68% vs 37%, p < 0.0001) and pre-treatment anemia and elevated NLR (PFS: 61% vs 30%, p < 0.0001; OS: 68% vs 37%, p < 0.0001). Five-year PFS (50% vs 31%) and OS (60% vs 36%) was better in patients whose pre-treatment anemia improved to normal hemoglobin levels on treatment vs those patients who were anemic both pre- and on-treatment. Conclusion: Pre-treatment and on-treatment anemia were significant, independent predictors of worse PFS and OS. Anemia and other hematologic parameters remain prognostic markers for cervical cancer patients. Improvement in PFS and OS was seen in patients with normalization of hemoglobin.